(3GdefUhQi aj GdWHs - (3eMeO Hf RcQjG GdnqQGRj, CHh HcQ,J (B311 (3g` s ((3GdbGgQI s)
(3ChdgG (B:s
(3GdbdH gi GdefaYI GdChdi GdJi aVd HgG GdMjhGf Ydi GdfHGJ hCeG GdefaYI GdJi efGdgG ef GdOeGZ GdJi dgG GdceGd s
(3BNQgG (B:s
(3aEPG bO CJjfG Ydi LejY gPg GdebGdGJ GdYTQ hGdaUhd GdePchQI bO jced cJGHfG HGdUdGI Ydi eMeO GdfHi hYdi Bdg GdCNjGQ GdWGgQjf hSde fLRJ GdebGdI GdYGTQI HJeGe GdcJGH s
(3hgh ai YTQI ebGdGJ ai LejY GdCOhGAs
(3Cdag ddCejQ efUhQ Hf ESMb Hf CMeO Hf CSO MGce GdQi ef SfI (B290 (3Edi (B296s
(3hWGdYg eMeO Hf eMeO GdgGOi GdcHjQ GdQGMdis
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs